2015
DOI: 10.1177/0042085915602538
|View full text |Cite
|
Sign up to set email alerts
|

From Alienation to Efficacy: An Examination of Racial Identity and Racial Academic Stereotypes Among Black Male Adolescents

Abstract: Black male adolescents face unique barriers in schools that may contribute to racial disparities in educational outcomes. Their social-cognitive strengths, however, influence their confidence to be academically successful despite these barriers. This study explored whether racial academic stereotypes and racial centrality were associated with and predicted school efficacy among 103 urban Black male adolescents. Findings indicated that racial centrality had the strongest relationship with and was the strongest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 84 publications
5
44
0
Order By: Relevance
“…The school safety discourse in the current study is not connected to guns or weapons, as shown in previous studies (Ellis et al 2015). Instead the present results are connected to a school safety discourse where drug addict students' unpredictable behaviour had an impact on school safety.…”
Section: Discussionsupporting
confidence: 69%
“…The school safety discourse in the current study is not connected to guns or weapons, as shown in previous studies (Ellis et al 2015). Instead the present results are connected to a school safety discourse where drug addict students' unpredictable behaviour had an impact on school safety.…”
Section: Discussionsupporting
confidence: 69%
“…The participants' belief in the ability to succeed was consistent with literature and findings from previous studies on academic achievement Apesin & Gong, 2018;Ellis, Rowley, Nellum, & Smith, 2018;White, Decuir-Gunby, & Kim, 2019).…”
Section: The Role Of Self-efficacy and Anti-deficit Mindsetsupporting
confidence: 87%
“…For Laurence, verbal persuasions came from his supervisor, who consistently encouraged him that he Participants' Sources of Self-Efficacy could go far in his career. Despite much of the research on self-efficacy among Black males being isolated to K-12 (Ellis, Rowley, Nellum & Smith, 2018;), there is an increasing amount of literature that finds self-efficacy critical for Black males as they navigate the educational pipeline beyond high school (Wood, Newman, & Harris, 2015;Tucker-Seeley, Mitchell, Shires, & Modlin, 2015).…”
Section: The Role Of Self-efficacy and Anti-deficit Mindsetmentioning
confidence: 99%
“…American research shows similar patterns for youth growing up in poor neighborhoods and especially for African American male students in regard to lack of academic performance, discipline difficulties, and distress. Furthermore, this group of students are more likely to be exposed to violence and categorized as suffering from a learning disability or having a diagnosis (Ellis, Rowley, Nellum, & Smith, 2015; Noguera, 2003; Peguero, 2011). There is also a strong connection between exposure to violence and students’ association with delinquent friends (Peguero, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%